A Final Word - Khong, Chooi Peng (Journal of Modern Languages, 2017)
The paper reviews all papers related to the University of Malaya Spoken English Project, i.e. UMSEP project, published in the special issue of the UMSEP, volume 3, 1985. It points out that UMSEP is the second international project undertaken by the Language Centre at the University of Malaya (UM). The paper mentions some factors towards the success of the UMSEP, such as viable testing programme.